Trends in functional programming 11th international symposium, TFP 2010, Norman, OK, USA, May 17-19, 2010. revised selected papers - Page, R.; Horváth, Zoltán; Zsók, Viktória (Lecture notes in computer science, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the 11th International Symposium on Trends in Functional Programming, TFP 2010, held in Norman, OK, USA, in May 2010. The 13 revised full papers presented were carefully reviewed and selected from 26 submissions during two rounds of reviewing and improvement. The papers cover new ideas for refactoring, managing source-code complexity, functional language implementation, graphical languages, applications of functional programming in pure mathematics, type theory, multitasking and parallel processing, distributed systems, scientific modeling, domain specific languages, hardware design, education, and test